Studi Komparatif Sistem Pendidikan Di Inggris,Belanda dan Jerman - Ahmad Zulfikar Fatah; Agustina Alvi Gunawan (An-Nahdhah: Journal of Education and Culture, 2025)
n an effort to improve the quality of human resources, education serves as one of the main pillars of sustainable societal development. This comparative study examines the education systems in the United Kingdom, the Netherlands, and Germany, focusing on each country's unique approach to managing education and the comparative outcomes that can enhance educational practices in other nations, including Indonesia. The analysis reveals that the education systems in these three countries, shaped by history, culture, and government policies, exhibit distinct characteristics. The United Kingdom implements a structured education system with national examinations, while the Netherlands emphasizes flexibility and inclusive education, and Germany adopts a dual education model that has successfully reduced youth unemployment. This study also provides recommendations for educational development in Indonesia based on the findings.